Final report - Ásgeir Atlason 1988-; Georg Styrmir Rúnarsson 1988- (2015)
The Icelandic Strætó app (http://www.straeto.is/app) is one of the more famous Icelandic applications in the country, allowing you to effectively construct and plan routes with respect to the bus network between destinations, view current bus locations in real time on a map and most importantly: purchase a ticket and then use it by showing the ticket on the phone with the app to the driver. At the time of writing, the Strætó application is only available for mobile devices using the more recent Apple and Android operating systems. Until recently, Android and Apple devices have dominated the smartphone market and have therefore been prioritized as platforms for the Strætó app. New developments, the release of the new Microsoft Windows 10 operating system and the subsequent push from Microsoft to make development tools easily available and supported for application development, have made Windows devices much more desirable for development. For these reasons Strætó bs. has been working with Stokkur Software ( the company that made and maintains the bus app on behalf of Strætó) and Opin Kerfi (a distribution partner for Windows devices in Iceland) to experiment with porting the current app to the Windows 10 platform. The team was offered the chance lead this first attempt, the goal being to get a working application including the core features such as buying and using tickets and also to document the experience working with the Windows Phone environment.